2012
DOI: 10.1051/0004-6361/201219023
|View full text |Cite
|
Sign up to set email alerts
|

Atomic data for astrophysics: Fe xii soft X-ray lines

Abstract: We present new large-scale R-matrix (up to n = 4) and distorted-wave (DW, up to n = 6) scattering calculations for electron collisional excitation of Fe xii. The first aim is to provide accurate atomic data for the soft X-rays, where strong decays from the n = 4 levels are present. As found in previous work on Fe x, resonances attached to n = 4 levels increase the cross-sections for excitations from the ground state to some n = 4 levels, when compared to DW calculations. Cascading from higher levels is also im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 28 publications
(34 reference statements)
2
30
0
Order By: Relevance
“…We have found the same issues we discovered in Fe x (Del Zanna et al 2012b) and found to be present in Fe xii (Del Zanna et al 2012a) and Fe xiii (Del Zanna & Storey 2012), i.e. resonance enhancement for some n = 4 configurations and levels is significant.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…We have found the same issues we discovered in Fe x (Del Zanna et al 2012b) and found to be present in Fe xii (Del Zanna et al 2012a) and Fe xiii (Del Zanna & Storey 2012), i.e. resonance enhancement for some n = 4 configurations and levels is significant.…”
Section: Discussionsupporting
confidence: 86%
“…The importance of resonance effects for the n = 4 levels was found when calculating atomic data for Fe x (Del Zanna et al 2012b), but was also found in Fe xii (Del Zanna et al 2012a) and Fe xiii . Here, we present new large-scale scattering calculations for the Fe xi soft X-ray lines.…”
Section: Introductionmentioning
confidence: 89%
“…For the Fe ions, the diagnostics are complicated further by the strong density sensitivity of many of the Fe emission lines. Although it was found that many of the standard EIS density diagnostics (e.g., Young et al, 2009;Watanabe et al, 2009;Del Zanna et al, 2012) do not depend strongly on κ or T , the uncertainties on the density measurements are passed on to the κ determinations, leading to greater uncertainty in derived values. Fe XVII was identified as the most useful Fe ion as the line ratios are insensitive to density, but the diagnostics were hampered by uncertainties in the atomic data.…”
Section: Diagnostics From Coronal Linesmentioning
confidence: 99%
“…Liang et al 2009Liang et al , 2010Liang et al , 2012O'Dwyer et al 2012;Del Zanna et al 2010, 2012aDel Zanna 2011a,b;Del Zanna et al 2012b;, 2013Del Zanna et al 2014). These calculations represent significant improvements to previous atomic data, since they include a large number of levels and the associated cascading and resonances.…”
Section: Introductionmentioning
confidence: 92%
“…(4)) for each ion are also provided (Del Zanna et al 2014, 2012aDel Zanna & Storey 2013;Del Zanna et al 2010, 2012b). …”
Section: Collision Strengths Datasetsmentioning
confidence: 99%